Pengembangan Aplikasi Digital Berbasis Artificial Intelligence Guna Efisiensi Pembuatan Akta Notaris - Melati, Putri (Jurnal Hukum Caraka Justitia, 2025)
The purpose of this research is to analyze the comparison of legal effectiveness between the conventional system and the Touch My Land digital system in making notarial deeds and formulate an ideal future regulatory concept related to the digitization of notarial services. The research method used is prescriptive normative legal research. First Research Result: The digital deed application can increase the efficiency of deed-making time from days to only a few hours. The rate of errors in writing news on the deed also greatly decreases; this proves the effectiveness of the data verification feature and the Artificial Intelligence-based editorial check. The application of the Artificial Intelligence-based digital deed application system in the Notary environment has great potential in supporting the digitization of legal services in Indonesia and increasing the speed and accuracy of services to the public. Second: The regulatory model needed is to update the Regulation of the Minister of ATR / BPN to regulate the complete procedure for integrating the digital deed system, then amend the Notary Position Law Article 16 paragraph (1) letter m concerning Physical Presence and the Electronic Information and Transaction Law in Article 5 paragraph (4) concerning the validity of electronic deeds so that notarial deeds can be made and recognized in electronic form and make the two rules harmonize to facilitate the application of digital applications based on Artificial Intelligence.